Аналіз систем керування процесами горіння на основі засобів комп’ютерного зору та обробки зображень - Арзікулов, Т. С.; Баган, Т. Г. (Vinnytsia National Technical University, 2023)
Trends in the world market to increase the energy efficiency and environmental friendliness of traditional means of obtaining energy, such as industrial boiler units, have caused the need for widespread implementation and use of the latest means of optimal management of these objects. More than 60% of the world's energy generation occurs through the process of burning fuel. In the Ukrainian scientific space, considerable attention is paid to analytical, predictive and fuzzy regulators as means of optimal management, and the use of a newer and more promising field of computer vision, which, in connection with the high level of development of information technologies in the country, is almost not represented, is quite promising for the future development of energy efficiency technologies, including in the export market. The article examines the process of development and formation of the modern direction of using computer vision tools to optimize the process of burning different types of fuel. The path and modern trends of development are considered. Over thirty-five years of research, significantly higher speed and a fairly wide range of analytical information, which can be presented by systems of this type compared to others, were noted. Starting with relatively simple single-parameter monitoring and optimization systems, which due to their speed were able to improve the flow of transient processes and made possible the use of systems in extreme mode, thirty years ago, to complex and multi-parameter systems that perform optimization based on a set of parameters, already after twenty years of research. Computer vision systems provide a wide range of analytical information that can be used both in the process of automatic control and to determine the quality indicators of boiler unit use.